A Case Report of a 10-Month-Old Child Diagnosed with Tricuspid Valve Atresia - Rabbani, Golam Mahfuz (Medicine Today, 2025)
Introduction: Tricuspid atresia (TA), a cyanotic form of congenital heart disease, is the absence of real or potential joining of the right atrium and right ventricle. This total absence of the right atrioventricular junction is typically caused by the regular position of the tricuspid valve, which forms a dimple close to the right atrium's floor exactly over the right ventricle. Case history: A 10-month-old male patient came to us with complaints of fever and respiratory distress. His oxygen saturation in room air was 76% with a heart rate of 130 and body temperature of 101 F. At first, he was diagnosed with pneumonia by a pediatrician. Then he came to me after not receiving any response from treatment. On examination I founded rhonchi and systolic murmur. So, our initial assessment involved taking CBC, x-ray and echocardiography of the patient's chest. The data from his echocardiography reveals that he has a tricuspid valve atresia. Conclusion: We decided to continue the conservative treatment for TVA with pneumonia (Paracetamol sos, Agoxin, Vitamin B complex for 6 months, and injectable antibiotic for 10 days) that started on him. After 11 months, the patient returned to us with RTI again. We treated his RTI with antibiotics. At the follow-up of the 12th month, his symptoms showed improvement. Medicine Today 2025, Vol.37 (1): 154-157